Paediatric varicella epidemiology in urban Beijing, China, 2014–2023 - Dan Yu; Wei Su; Miao Fan; Lu Lu; Xinyu Wang; Sheng Zhang; Qingjing Du; Lin Ma; Ying Liu; Kaihu Yao (Emerging Microbes and Infections)
Data on the clinical epidemiology of varicella in Beijing, China, remain limited. Here, we present an analysis of paediatric varicella cases from 2014 to 2023, including 10,049 cases from two children's hospitals. A gradual decline in the number of varicella cases over this period, with a marked decrease in 2020 coinciding with non-pharmaceutical interventions implemented during the COVID-19 pandemic was observed. Notably, seasonal patterns of varicella incidence weakened after 2019. Although children under four years of age accounted for the majority of cases (57.5%), the proportion of adolescents (13–18 years) increased in 2023. Our findings underscore the need for broader vaccination coverage and enhanced laboratory diagnostics to achieve effective varicella control.